Optimal Sizing of the Stand-Alone Photovoltaic System for a Solar-Powered Translational Sprinkler Irrigation Machine considering the Loss of Power Supply Probability. (19th January 2022) - Liu, Kenan; Sun, Bugong; Gao, Xiaoyang; Zhang, Yang; Sun, Wei; Feng, Quan; Yang, Wanxia
Abstract : The translational sprinkler irrigation machine is widely used because of its high degree of automation, less manual investment, and convenient movement. However, when using the sprinkler irrigation machine, the power supply is difficult to be guaranteed in some remote power shortage areas. Solar energy has become one of the best choices for the power source of sprinkler irrigation machines. An important issue is the optimal sizing of the stand-alone photovoltaic system for a solar-powered translational sprinkler irrigation machine. This work conducts the optimal sizing of the stand-alone photovoltaic system for a solar-powered translational sprinkler irrigation machine considering the loss of power supply probability. Firstly, the self-developed translational sprinkler irrigation machine is introduced. The load power, which includes the driving power of the translational sprinkler irrigation machine, water intake pressure driving power, and the loss power of the controller and sensors, is considered in the calculation process. Subsequently, the photovoltaic generator model and the battery storage model are established. Then, the stand-alone photovoltaic system is optimized considering the loss of power supply probability (LPSP) and the life cycle cost (LCC). After the solar irradiance and ambient temperature of a typical sunny day in the test area are given, the optimal combination of the PV module and battery is obtained. The optimal sizing result is verified using the PV power, state of charge (SOC), and load power. The presented optimal sizing method is also compared with an existing method. Besides, the operation test of the sprinkler irrigation machine is also carried out to verify the optimal sizing result. The optimal sizing result is proved to be effective and applicable.